2017
DOI: 10.1016/j.gie.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The cost-effectiveness of radiofrequency ablation for Barrett's esophagus with low-grade dysplasia: results from a randomized controlled trial (SURF trial)

Abstract: Background and Aims: The Surveillance versus Radiofrequency Ablation (SURF) trial randomized 136 patients with Barrett's esophagus (BE) containing low-grade dysplasia (LGD), to receive radiofrequency ablation (ablation, n Z 68) or endoscopic surveillance (control, n Z 68). Ablation reduced the risk of neoplastic progression to highgrade dysplasia and esophageal adenocarcinoma (EAC) by 25% over 3 years (1.5% for ablation vs 26.5% for control). We performed a cost-effectiveness analysis from a provider perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…The results of this study align with the previous literature which has shown RFA to be cost effective for LGD and HGD separately [22,25,39]. Although the previous analysis of RFA for only HGD patients resulted in a marginally lower ICER (£1,272) [39], the current analysis highlights that use of RFA for both LGD and HGD patients remains significantly cost-effective (ICER: £3,006).…”
Section: Accepted Manuscript 4 Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results of this study align with the previous literature which has shown RFA to be cost effective for LGD and HGD separately [22,25,39]. Although the previous analysis of RFA for only HGD patients resulted in a marginally lower ICER (£1,272) [39], the current analysis highlights that use of RFA for both LGD and HGD patients remains significantly cost-effective (ICER: £3,006).…”
Section: Accepted Manuscript 4 Discussionsupporting
confidence: 88%
“…LGD patients with a confirmed diagnosis on two separate occasions [17,21] as studies suggest that surveillance is less effective than RFA in preventing disease progression [22].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The previously described data on costeffectiveness also factored into this risk-to-benefit assessment. 30,31 There are limited to no data addressing the issue of patient preferences and burden and inconvenience associated with either of these treatment approaches.…”
Section: Resultsmentioning
confidence: 99%
“…Data from a recent RCT showed that ablation with RFA for patients with confirmed LGD is more effective and more expensive than surveillance in reducing the risk of progression to the endpoint of HGD/EAC. 31 Similarly, a decision analysis that compared cost-effectiveness of esophagectomy and EET in the treatment of early EAC showed that EET was more effective and less expensive than esophagectomy. 32 EET was also a cost-effective alternative in patients with submucosal cancer, especially in patients with high operative risk.…”
Section: Policymakersmentioning
confidence: 99%
“…However, recent evidence has confirmed the long-term efficacy and safety of RFA for the treatment of LGD (14,31,32) and this has been acknowledged by health technology evaluation agencies (3). The analysis presented here used a different pattern of clinical practice but was similar to studies carried out in the USA (27,29) and Europe (30,33). These studies have shown that RFA-EMR with SoC was a cost-effective strategy compared to SoC alone in BE patients with…”
Section: Discussionmentioning
confidence: 92%